Interfaith Marriage And Its Legal Consequences For Children Born According To Islamic Law - Hastuti , Indira; Sanjaya, Edy; Prasetyo, Budi (International Journal of Educational Research & Social Sciences, 2022)
Interfaith marriages, which are widely practiced in society, will, in the long term, have a social and psychological impact on children born to these couples. In contrast, in terms of legal aspects, they certainly have legal consequences for children born to couples of different religions. The purpose of this study was to determine the legal implications of interfaith marriages for children born according to Islamic law. Methods This study uses a normative juridical method by reviewing various literature relevant to the studied theme. Data was collected through a literature study to find secondary legal materials pertinent to the prescriptive descriptive approach. The study results indicate that the legal consequences of interfaith marriages are invalid marriages, and children born are not permitted according to Islamic law. According to Islamic law, Interfaith marriages have legal implications for children who are born; namely, children are considered as children born out of wedlock. Children born out of wedlock only have a kinship relationship with their mother and their mother's family.